2023
DOI: 10.1186/s12887-023-03878-6
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth and atopic dermatitis in early infancy: results from the Japan Environment and Children’s Study

Abstract: Background Atopic dermatitis (AD) is reported to be more prevalent in children who were born in autumn than in spring. Here, we investigated how early the association between season of birth and eczema or AD can be observed in the postnatal period. We also examined whether specific prevalence outcomes for infant eczema and AD differed according to sex and maternal history of allergic disease in a large Japanese cohort. Methods Using data of 81,615 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…8 A study conducted in Japan found that EBF for at least six months was associated with a lower risk of AD (OR 0.70; 95% CI 0.52-0.93). 9 While the protective effect of breastfeeding against AD has been reported in many studies, there is limited research on this topic in Saudi Arabia, particularly in the Al Madinah region (AL-Hijaz area of Western Saudi Arabia). This is the desert region where the summers are harsh, and there is no humidity in the area.…”
Section: Introductionmentioning
confidence: 99%
“…8 A study conducted in Japan found that EBF for at least six months was associated with a lower risk of AD (OR 0.70; 95% CI 0.52-0.93). 9 While the protective effect of breastfeeding against AD has been reported in many studies, there is limited research on this topic in Saudi Arabia, particularly in the Al Madinah region (AL-Hijaz area of Western Saudi Arabia). This is the desert region where the summers are harsh, and there is no humidity in the area.…”
Section: Introductionmentioning
confidence: 99%